2022
DOI: 10.1021/acssuschemeng.2c01576
|View full text |Cite
|
Sign up to set email alerts
|

Facile One-Pot Synthesis of Furan Double Schiff Base from 5-Hydroxymethylfurfural via an Amination–Oxidation–Amination Strategy in Water

Abstract: Furan double Schiff base (FDSB), a versatile biomass fine-chemical molecule, was efficiently synthesized from 5hydroxymethylfurfural (HMF) through an amination−oxidation−amination strategy in water. The activated α-MnO 2 -S-H + with a higher specific surface area, more surface lattice oxygen vacancies, and abundant acid/base sites exhibited a high catalytic efficiency. An FDSB yield of 99.3% with 100% conversion of HMF using air−oxygen as the oxidant was achieved within 20 min in water. The oxidation of the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Bio-based plastics can have positive impacts on the environment by reducing carbon emission, if produced from sustainable resources by green processes. ,,, However, to make a real impact, they need a sustainable and managed end of life. They must from the start be designed for chemical, mechanical, and/or organic (biological) recycling. , Developing energy-efficient and selective chemical recycling processes is a necessary part of achieving truly circular plastic flows. , Polyesters are well suited for chemical recycling due to the presence of reversible ester linkages. ,,,,,, The use of dynamic covalent chemistry to include a second, even more easily reversible bond, such as a Schiff base (SB, i.e., imine bond), can further facilitate chemical recycling back to monomers under mild conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…Bio-based plastics can have positive impacts on the environment by reducing carbon emission, if produced from sustainable resources by green processes. ,,, However, to make a real impact, they need a sustainable and managed end of life. They must from the start be designed for chemical, mechanical, and/or organic (biological) recycling. , Developing energy-efficient and selective chemical recycling processes is a necessary part of achieving truly circular plastic flows. , Polyesters are well suited for chemical recycling due to the presence of reversible ester linkages. ,,,,,, The use of dynamic covalent chemistry to include a second, even more easily reversible bond, such as a Schiff base (SB, i.e., imine bond), can further facilitate chemical recycling back to monomers under mild conditions. , …”
Section: Introductionmentioning
confidence: 99%
“…Increasingly severe warming of the global climate and swift depletion of fossil fuels have stimulated the development of sustainable and renewable bioresources to replace the current fossil energy economy. Cost-effective utilization of available renewable lignocellulose (LC) to manufacture valuable chemicals may alleviate the resource/energy crisis and environmental pollution. Hemicellulose is an important polysaccharide in biomass, which can be used as feedstock for furfural (FAL) production . FAL is a versatile molecule that not only can be used to manufacture a series of furan derivatives, fine chemicals, biofuels, fuel additives, resins, plastics, fungicides, and nematicides , but also can be utilized as an industrial solvent for lubricating oil refining .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, such resin is not suitable for application as wood adhesive, but different resins will be obtained by combining MH polymer with glyoxal. It is known that aliphatic amines can react with aldehydes to form Schiff base, but stable Schiff base is generally formed between amines and aromatic aldehydes (like benzaldehyde or furfural , ) as such Schiff bases are conjugated species. A recent study on tannin-MH system has shown that MH polymers are reactive toward quinone species .…”
Section: Introuctionmentioning
confidence: 99%